1956
DOI: 10.1037/h0041255
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of interresponse times upon the relative reinforcement of different interresponse times.

Abstract: The literature contains indications that the time intervals between responses, i.e., the interresponse times (IRTs), made by rats depend on which IRTs have been followed more often by food reinforcements. In the present study evidence on the occurrence and nature of this dependence was obtained by comparing IRT distributions with reinforced-IRT distributions, and by altering the allocation of reinforcements to IRTs (reinforcement of an IRT refers to reinforcement of the terminal response of that IRT).The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
280
2

Year Published

1968
1968
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(291 citation statements)
references
References 5 publications
9
280
2
Order By: Relevance
“…A more sensitive method of estimating the probability of response as a joint function of stimulus value and time since preceding response makes use of Anger's (1956) IRTs/Op statistic (Blough, 1969). Anger (1956) argues that because there are more opportunities for short IRTs than for long IRTs, the relative frequency of occurrence of a given IRT should be assessed in relation to the opportunity that the IRT may occur.…”
Section: Victoria University Of Wellington Wellington New Zealandmentioning
confidence: 99%
See 1 more Smart Citation
“…A more sensitive method of estimating the probability of response as a joint function of stimulus value and time since preceding response makes use of Anger's (1956) IRTs/Op statistic (Blough, 1969). Anger (1956) argues that because there are more opportunities for short IRTs than for long IRTs, the relative frequency of occurrence of a given IRT should be assessed in relation to the opportunity that the IRT may occur.…”
Section: Victoria University Of Wellington Wellington New Zealandmentioning
confidence: 99%
“…Anger (1956) argues that because there are more opportunities for short IRTs than for long IRTs, the relative frequency of occurrence of a given IRT should be assessed in relation to the opportunity that the IRT may occur. In a given IRT class interval, the number of opportunities for an IRT is the number of IRTs in that interval plus the number of longer IRTs.…”
Section: Victoria University Of Wellington Wellington New Zealandmentioning
confidence: 99%
“…What is needed here is an index of the conditional probability of performing a response in the WS interval, provided that the opportunity occurs. This is the same index that Anger (1956) termed the "IRT/Op.," or the likelihood of response in a certain interresponse interval, given an opportunity in that interval. For subjects having a WS, the conditional probability of responding in the WS interval is essentially the same as the traditional measure used in discretetrials signaled avoidance, i.e., the number or proportion of avoidances in successive equal blocks of training trials.…”
Section: Procedun! and Designmentioning
confidence: 99%
“…After 17 sessions were carried out, the CR was recovered. With respect to the temporal discrimination function, there have been many studies of timing behavior in rats using the differential reinforcement of low res ponse rate schedule (Anger 1956, Kelleher et al 1959, Ellen et al 1964, Ellen and Butter 1969. These studies and others on monkeys (Brady andConrad 1960, Stamm 1963) or rabbits (Suzuki and Saito 1970) have consistently indicated that animals responded at very short inter-response times in earlier stages of the training, and as the training progressed they tended to show longer inter-response times in accordance with requirements of the schedule.…”
Section: Augmentation Of Visual Evoked Potentials By Pairing Photic Smentioning
confidence: 99%